Assessment of the impact of removable denture's care agents on the mechanical properties of selected acrylic resins – based on pilot studies - Krupińska, Karolina; Gala, Andrzej; Wiśniewska, Grażyna (Journal of Stomatology, 2017)
Introduction. Removable acrylic dentures are the most commonly used prosthetic restorations. Their use involves daily hygienic care with cleaning agents and disinfectants. There are many uncertainties regarding the effect of disinfectants on the mechanical properties of acrylics. Aim of the study. To assess in vitro whether acrylic denture disinfectants have an effect on the hardness and tensile strength of acrylic materials. Materials and methods. The study was conducted with two acrylic materials of which removable dentures are commonly made, i.e. SR Triplex Hot from Ivoclar Vivadent and Rapid Simplifield from Vertex. The following preparations used for the disinfection of dentures were assessed: 2% chlorhexidine gluconate solution, 2% sodium hypochlorite solution, Corega Tabs cleansing tablets and Fittydent cleansing tablets. Twenty-four samples were made from each material. The samples were divided into three groups. In the first group, samples were stored in distilled water at 37°C and dipped in one of the four disinfectants for 15 minutes once a day. In the second group, samples were stored in distilled water and they were not disinfected. In the third group (control group), samples were tested right after they were made. After 2 and 4 weeks, samples in the first and second groups were tested for hardness and tensile strength. Tensile strength was tested using a universal testing machine, and hardness was tested using a hardness gauge (Vickers method). The results obtained were analysed statistically. Findings. Chlorhexidine was the solution that reduced the hardness and strength of acrylic the most. The smallest drop in the strength properties of acrylic was observed for Fittydent and Corega Tabs cleansing tablets and sodium hypochlorite solution. Conclusions. All the acrylic disinfectants used reduced the mechanical properties of acrylic.